Problems Updating the Professional Standard “Accountant” - Vladimir I. Barilenko (Учёт. Анализ. Аудит, 2019)
The article continues the discussion on issues of development, perfection and practical application of professional standards. Raised the question interconnected updating professional standard “Accountant” and educational programs for preparation accounting staff. It critically discusses taken now the main approaches to the evaluation of proposals for changes in professional standards and proposes measures to improve the adequacy of the provisions of the standard “resume” the requirements of employers and the real needs of the practice of economic work. It proved the feasibility of a broad interpretation of the role and functions of the accountant in this standard, as well as the inability to meet the requirement of the universal applicability of labor accounting functions for all organizations, regardless of their scale of operation and organizational legal form. The necessity to ensure compliance with the standard set forth in the “Accountant” qualification requirements and are able to ensure their educational programs.